A review of communication and patient safety - Abdullah, Siti Nur Dini; Ruslan, Rusila (IIUM Press, 2024)
Background: Addressing and improving communication skills among healthcare professionals is crucial not only for enhancing patient satisfaction but also for promoting positive health outcomes and overall healthcare quality. Therefore, this review aims to understand the communication skills among nursing and healthcare personnel. Methods: The PICO format is employed to articulate the components of a well-structured clinical question, guiding the exploration of pertinent evidence for the literature review. Results: A collective of 25 literature subjects relevant to the research topic were identified. The review yielded four main themes: (1) Establishing the definition of poor communication, (2) Underscoring the significance of communication skills, (3) Examining the impact of poor communication on patient safety, and (4) Identifying factors associated with inadequate communication. Conclusion: In summary, this review highlights the crucial need to understands the communication level of the nursing and healthcare personnel in ensuring patient safety.